2005
DOI: 10.3171/sup.2005.102.s_supplement.0147
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife surgery for brain metastases in patients harboring four or more lesions: survival and prognostic factors

Abstract: Object. This study was performed to evaluate the role of gamma knife surgery (GKS) in patients with a large number (four or more) of metastatic brain lesions. Methods. The authors retrospectively reviewed the outcome in 130 patients who underwent GKS for metastatic lesions. Eighty-four patients presented with one to three lesions (Group A) and 46 presented with four or more lesions (Group B). The overall median survival time after GKS was 35 weeks. The median survival time in Group A (48 weeks) was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The median survival of 11.9 months in the current series with radiosurgery compares favorably with historical surgical series. The efficacy of radiosurgery for patients with a brain metastasis is well established (18)(19)(20)(21)(22)(23)(24). Local tumor control after radiosurgery is not dependent on the histology of the tumor.…”
Section: Discussionmentioning
confidence: 98%
“…The median survival of 11.9 months in the current series with radiosurgery compares favorably with historical surgical series. The efficacy of radiosurgery for patients with a brain metastasis is well established (18)(19)(20)(21)(22)(23)(24). Local tumor control after radiosurgery is not dependent on the histology of the tumor.…”
Section: Discussionmentioning
confidence: 98%
“…[26][27][28][29][30][31][35][36][37][38][39][40][41] These reports suggest that SRS is more effective than WBRT and that it is comparable to or superior to surgery. [26][27][28][29][30][31][32][35][36][37][38][39][40][41][42][43] SRS as the sole initial management or as a boost before or after WBRT has emerged as a widely practiced treatment modality for brain metastases. The goal of SRS without WBRT is to achieve brain control without the possible long-term neurotoxic or cognitive side effects of WBRT.…”
Section: Nonrandomized Studies Of Srs For Metastatic Brain Tumorsmentioning
confidence: 98%
“…[26][27][28][29][30][31]33,[35][36][37][38][39][40][41][58][59][60] In addition to systemic disease status, other factors may contribute to the discrepancy between the high rate of local tumor control and the lower rates of survival. Other retrospective studies reported median survivals to range from 8 to 15 months.…”
Section: Overall Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…This survival difference did not reach statistical significance. Nam et al [19] retrospectively compared a cohort of patients with one to three metastases to a cohort with four or more metastases. The group with fewer brain metastases had a significantly longer median survival; however, on multivariate analysis, RPA class was the only significant prognostic factor identified.…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%